Targeting fibroblast growth factor (FGF)-inducible 14 (Fn14) for tumor therapy - Zaitseva, Olena; Hoffmann, Annett; Otto, Christoph; Wajant, Harald (Frontiers in Pharmacology, 2022)
Fibroblast growth factor-inducible 14 (Fn14) is a member of the tumor necrosis factor (TNF) receptor superfamily (TNFRSF) and is activated by its ligand TNF-like weak inducer of apoptosis (TWEAK). The latter occurs as a homotrimeric molecule in a soluble and a membrane-bound form. Soluble TWEAK (sTWEAK) activates the weakly inflammatory alternative NFkappaB pathway and sensitizes for TNF-induced cell death while membrane TWEAK (memTWEAK) triggers additionally robust activation of the classical NFkappaB pathway and various MAP kinase cascades. Fn14 expression is limited in adult organisms but becomes strongly induced in non-hematopoietic cells by a variety of growth factors, cytokines and physical stressors (e.g. hypoxia, irradiation). Since all these Fn14-inducing factors are frequently also present in the tumor microenvironment, Fn14 is regularly found to be expressed by non-hematopoietic cells of the tumor microenvironment and most solid tumor cells. In general, there are three possibilities how the tumor-Fn14 linkage could be taken into consideration for tumor therapy. First, by exploitation of the cancer associated expression of Fn14 to direct cytotoxic activities (antibody-dependent cell-mediated cytotoxicity (ADCC), cytotoxic payloads, CAR T-cells) to the tumor, second by blockade of potential protumoral activities of the TWEAK/Fn14 system, and third, by stimulation of Fn14 which not only triggers proinflammtory activities but also sensitizes cells for apoptotic and necroptotic cell death. Based on a brief description of the biology of the TWEAK/Fn14 system and Fn14 signaling, we discuss the features of the most relevant Fn14-targeting biologicals and review the preclinical data obtained with these reagents. In particular, we address problems and limitations which became evident in the preclinical studies with Fn14-targeting biologicals and debate possibilities how they could be overcome.